A Nicaraguan/Guatemalan Encuentro: Villagers Hosting International Service Learning Groups Reflect on Their Experiences - O'Sullivan, Michael; Smaller, Harry; Heidebrecht, Luke; Balzer, Geraldine (Canadian Journal of Education/Revue canadienne de l'éducation, 2019)
In August 2017, 27 residents from four Nicaraguan and four Guatemalan communities met in Managua, Nicaragua, to discuss their experiences hosting International Service Learning (ISL) groups from the Global North. Despite having many positive recollections, these host community representatives identified a number of issues of concern. This article describes the background to this encuentro (gathering), the issues raised, and the solutions identified in order to encourage Global South host organizations to become better able to articulate their expectations of their Northern visitors and to insist that Northern-sending agencies become more responsive to the expectations of their Southern hosts. Keywords: North–South partnerships, Southern epistemologies, international service learning, short-term study abroad, experiential education